2009
DOI: 10.1158/0008-5472.can-09-2266
|View full text |Cite|
|
Sign up to set email alerts
|

Glioblastoma Cells Require Glutamate Dehydrogenase to Survive Impairments of Glucose Metabolism or Akt Signaling

Abstract: Oncogenes influence nutrient metabolism and nutrient dependence. The oncogene c-Myc stimulates glutamine metabolism and renders cells dependent on glutamine to sustain viability (''glutamine addiction''), suggesting that treatments targeting glutamine metabolism might selectively kill c-Myc-transformed tumor cells. However, many current or proposed cancer therapies interfere with the metabolism of glucose, not glutamine. Here, we studied how c-Myc-transformed cells maintained viability when glucose metabolism … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
351
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 378 publications
(374 citation statements)
references
References 45 publications
20
351
0
3
Order By: Relevance
“…The amino acid glutamine can be incorporated into the mitochondrial Krebs cycle and can be used to generate fatty acids, nucleotides and energy. When deprived of glucose, glioblastoma cells have been shown to turn to glutamine utilization, and if glutamine metabolism is impaired, cells cannot survive in the absence of glucose (Yang et al, 2009). Thus, when glucose is not available, cells turn to amino acids and fatty acids to try to maintain energy levels and homeostatic functions.…”
Section: Sensing Glucose Deprivationmentioning
confidence: 99%
“…The amino acid glutamine can be incorporated into the mitochondrial Krebs cycle and can be used to generate fatty acids, nucleotides and energy. When deprived of glucose, glioblastoma cells have been shown to turn to glutamine utilization, and if glutamine metabolism is impaired, cells cannot survive in the absence of glucose (Yang et al, 2009). Thus, when glucose is not available, cells turn to amino acids and fatty acids to try to maintain energy levels and homeostatic functions.…”
Section: Sensing Glucose Deprivationmentioning
confidence: 99%
“…Moreover, glutamate can enter into mitochondria and be oxidized to α-ketoglutarate (α-KG), reducing NADP + to NADPH or NAD + to NADH and produces a second molecule of NH 4+ . This reaction is catalyzed by the glutamate dehydrogenase (GDH) which also plays a pivotal role in cancer survival [36]. GDH is the unique enzyme that can use NADP + or NAD + as cofactor.…”
Section: Glutamine Metabolismmentioning
confidence: 99%
“…In fact, some studies have shown unquestionable evidence that targeting glutamine metabolism, like blocking mitochondrial GLS1 activity, could be used to suppress tumor cell growth and transformation [36,46]. However, recent findings have suggested that even silencing GLS1 could suppress, but not eliminate, glioblastoma cell growth in vitro and in vivo.…”
Section: Mycmentioning
confidence: 99%
See 2 more Smart Citations